2002
DOI: 10.1021/nl020259a
|View full text |Cite
|
Sign up to set email alerts
|

Tris(hydroxymethyl)phosphine-Capped Gold Particles Templated by DNA as Nanowire Precursors

Abstract: Tris(hydroxymethyl)phosphine-capped gold nanoparticles (ca. 1−2 nm diameter) bind densely to DNA, although both species are negatively charged. The particles are also active catalysts for electroless plating of gold. Electroless plating after adsorption to calf thymus DNA immobilized on silicon provides nanowires as narrow as ca. 30−40 nm and electrical conductivities ca. one-thousandth that of bulk gold. Here we summarize our physical characterization of the particles and their DNA conjugates and initial elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
152
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 27 publications
5
152
0
2
Order By: Relevance
“…While this article was in preparation, nanowires were produced by electroless gold plating of DNA and reported to have conductive properties similar to those of metallized NM fibers (23). Just as plastic films and glass may share an important physical property (transparency) but differ in other ways that make them suitable for different purposes, wire templates formed by DNA and amyloid protein fibers have similar conductive properties but are so fundamentally different in other ways that they will be suited to different purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this article was in preparation, nanowires were produced by electroless gold plating of DNA and reported to have conductive properties similar to those of metallized NM fibers (23). Just as plastic films and glass may share an important physical property (transparency) but differ in other ways that make them suitable for different purposes, wire templates formed by DNA and amyloid protein fibers have similar conductive properties but are so fundamentally different in other ways that they will be suited to different purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The first biomolecular templates used for microstructures were phospholipid tubules (18), and since then other selfassembling rod-like structures have been assessed for their strengths and weaknesses as nanostructural templates, including DNA, bacteriophages, and microtubules (2,3,5,9,13,14,(19)(20)(21)(22)(23)(24). These materials have many positive characteristics as nanostructure materials.…”
mentioning
confidence: 99%
“…2 In this paper, we support the proposition that DNA molecules are ideal templates for bottom-up nanofabrication. [3][4][5][6][7] Previous work has demonstrated that DNA satisfies the last of these requirements as a template. For example, Keren et al showed that sequence-specific molecular lithography is possible; they used proteins that bind to specific sites on DNA to create patterns of metal coatings on single molecules of DNA.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Molecular combing is a widely used technique for stretching, patterning, and immobilizing DNA molecules onto a flat solid surface by a dewetting process. 5 However, the application of this technique is limited by the poor control of locations and lengths of the stretched DNA.…”
Section: Introductionmentioning
confidence: 99%